Peut-on dynamiser le travail des étudiants en Licence? - François Agnès; Diane Leduc; Morgane Locker (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
In this paper, we present a feedback of active pedagogy with flipped teaching, carried out with undergraduate students in Life Sciences (second year of bachelor's degree; University Paris-Saclay, France). In a teaching context where biology programs are very busy, our students are subjected to significant cognitive overload, associated with difficulties to sort out and mobilise information, and a global lack of scientific methodological training. How combining the necessary assimilation of knowledge, vocabulary and basic concepts and the acquisition of higher-level cognitive skills (to describe, analyse, interpret, represent, model, link facts together ...)? More generally, how can we motivate students, empower them in their learning and boost their work? Facing these questions, our educational team has been experimenting for several years with active and reverse learning at Master level. We wanted to assay its applicability in a bachelor's degree, where the success of the greatest number of students is a major issue for the university, while constituting one of its main challenges (Annoot, 2012). With the aim of reinforcing motivation, volition and cognition (Houart, 2017), we designed and deployed for two consecutive years, a hybrid pedagogical device based on the alternation of distant assimilation phases and face-to-face applications (Charlier et al., 2006). Analysis of its benefits, carried out through questionnaires submitted to students, indicates a very strong support on their part to the process, increased motivation to work and a feeling of methodological progress.